Bittersweet - Steel, Danielle (London Bantam Books, 1999)
After 17 years of marriage a mother of four decides to put some spark in her life and returns to her old job of photojournalist. The novel describes her adventures and romance with a Wall Street billionaire.
Keywords: Man-woman relationships -- Connecticut -- Women journalists